Back projection algorithm‐based GEO SAR real‐time quick Look imaging system. Issue 19 (31st July 2019) - Zhang, Qingjun; Li, Tengfei; Zhu, Yu; Yu, Zhongjiang; Ding, Zegang; Guo, Xin; Lv, Zheng
Abstract : Geosynchronous earth orbit synthetic aperture radar (GEO SAR) has the advantages of short revisit period and wide observation range. However, compared with low earth orbit SAR (LEO SAR), GEO SAR has the distinct characteristics of long synthetic aperture time, large amount of data, curvilinear motion trajectory, slow satellite speed, and long signal return delay etc. Hence, in this paper, a generalisation design technique of real‐time quick look imaging systems for both GEO SAR and LEO SAR is first proposed. Then, we present the corresponding system structure and its components. Finally, based on back projection algorithm (BPA), the validity of this quick look imaging system is verified by the simulation.